Stagnasi Agama dalam Pusaran Kapitalisme di Kabupaten Sumenep (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
Contemporary issues persist throughout human history, prompting religion to participate and offer solutions to the prevalent problems. Religion must play a significant role in resolving humanitarian issues. The exploitative practices of the capitalist system and human alienation from society need to be confronted with a revolutionary understanding of religion. Islam, in particular, possesses a spirit of liberation to uplift and advocate for the oppressed. This research aims to examine the religious understanding of the Sumenep community amidst the development of capitalism and ongoing development. It also seeks to explore the role of religion in liberating individuals from various threats of globalization and shielding them from various forms of social sins. The research employs a qualitative method with a descriptive approach, aiming to depict and summarize various conditions, situations, and variables that arise within society. To better understand the desired outcomes of this method, a social approach is employed. Consequently, liberation theology offers a paradigm to rectify the social system that has been damaged by various human-made systems and ideologies, in order to enhance the community's struggle in critically addressing these issues.